THE USE OF CUE CARDS FOR TEACHING WRITING OF BIOGRAPHY TEXT - Ulya Maliyatika; Muh Syafei; Rusiana Rusiana (Universitas Muria Kudus, 2018)
Students at schools learn to write in order to express their ideas well. They should have a good ability in writingEnglish texts. However, many students find it difficult to express their ideas in a paragraph, and to make a composition correctly. The media factorseems to be one that makes the teaching-learning process unable to achieve its goal. Therefore, the authors propose to apply Cue Cards as teaching media to overcome the problem.The objective of the research is to scrutinize whether there is a significant difference between teaching writing of biography textbefore and that after being taught by using Cue Cards.This experimentemployed one group with pretest and posttest design was conducted at the eleventh grade students of SMA N 1 KaranganyarDemakin academic year 2017/2018 insecond semester. There were 34 students of grade XI IPS 1 taken as the sample through cluster random sampling.The datasetsfor this research were collected through written test. Before cue cards were used in the treatment, the measn score was60. After cue cards were used in some meetings of treatment, the mean score is 82. The hypothesis of the research stated that there is a significant difference between teaching writing of biography text on the eleventh grade students of SMA N 1KaranganyarDemak in academic year 2017/2018) before and after being taught by using cue cardsis confirmed. It can be seen from the calculation of t-test, withdegree offreedom (df) = 33, α = 0,05, t (critical) is ±2.042 and t (obtained) is 8.79. The analysis showed that Ho was denied and Ha was confirmed.Therefore, it is suggested to the English teacherto keep usingcue cardsin teaching writing of biography text.